Molecular Docking of Brazilin from Secang Wood Plant (Caesalpinia sappan L.) as an Anti-Breast Cancer - Astriany, Dewi; Baroroh, Umi; Umam, Khotibul (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2024)
Breast cancer is a disease characterized by abnormal cell growth, which can invade adjacent tissues or metastasize to other organs. Secang (Caesalpinia sappan L.) is a plant that has been used as an alternative medicine for a variety of health conditions, including some types of cancer. This study aims to determine whether the brazilin compound found in secang wood can interact with the target receptors estrogen alpha, 17-β-HSD-1, and NUDT5, potentially serving as an anticancer candidate. Molecular docking simulations were employed to identify the molecular interactions of brazilin against estrogen receptor alpha (ERα) (PDB ID: 3ERT), 17β-HSD-1 (PDB ID: 3HB5), and NUDT5 (PDB ID: 5NQR) using AutoDockTools software. The results showed that the best free-binding energy (ΔG) value obtained for brazilin against the 17-β-HSD-1 receptor was -9.16 kcal/mol, with an inhibition constant of 192.45 nM. The ΔG value of brazilin with estrogen alpha was -6.68 kcal/mol, and the ΔG value for brazilin against NUDT5 was -4.8 kcal/mol. Brazilin has a higher potency compared to innate ligands based on the docking result of estrogen alpha receptor and NUDT5. Some structural similarities and interactions occurred between the amino acids GLY186 and TYR155 in brazilin with the binding of amino acids formed in the innate ligand against the 17-β-HSD-1 receptor, thus showing similar affinity to the 17-β-HSD1 receptor. In silico approaches provided valuable insights into the potential of brazilin as an anti-breast cancer agent.